Assessment of Executive Functions in School Considering Motor and Sociodemographic Factors: A Joint Vision for School-Based Occupational Therapists and School Staff - María José López-; Víctor Berdejo; Silvia Madrona-Velasco; Laura Gonzalo-Ciria; Laura Lasso-Olayo; Carmen López- (MDPI AG, 2024)
Executive functions (EFs) and motor skills are essential for many school and daily tasks. Many school-based occupational therapists need help addressing EFs. The current study aims to provide new insights into the relationship between executive functions and motor development by considering confounding factors. Ninety-six second-grade children were tested in one state-funded (public) school and another state-subsidised private school. Children were assessed with the Movement Assessment Battery for Children-2 (MABC-2), Neuropsychological Assessment of Executive Functions in Children, and Test of Perception of Differences-R. Families completed a sociodemographic questionnaire, and teachers completed a previous questionnaire and subsequently evaluated the information the occupational therapist provided. Mixed results were obtained regarding the correlation between motor and executive skills. Furthermore, children who received worse scores on the MABC-2 had more difficulties on the EFs tests. The Impulsivity Control Index was not correlated with any motor variable. Our results show that sociodemographic variables (except gender) correlate more with EFs than motor skills. The teachers showed a high degree of agreement with the occupational therapist (4.0 ± 0.8), even in children with good academic performance. They expressed the need for additional training and classroom interventions. A joint vision of motor-executive functioning can facilitate the design of effective interventions, especially in schools with more disadvantaged populations.